Skills Employers Seek : Results of the Armenia STEP Employer Skills Survey - Rutkowski, Jan J. (World Bank, Washington, DC, 2015)
The note presents the results of the STEP employer skills survey. The survey was implemented in early 2013 using a stratified sample of 354 firms. The firms were stratified by activity and firm size, with a booster sample of large firms. Post-stratification weights were used to make the results representative of firm size. The structure of the sample by activity, size and some other characteristics is presented in annex one. The small sample size implies that the estimates are subject to a wide margin of error. This problem is mitigated by the fact it is qualitative rather than quantitative results that are of primary interest. One should bear in mind that the survey’s results represent subjective perceptions, and as such should be taken with a grain of salt (for example, the employers may express exaggerated views). There are some additional limitations resulting from the survey’s design. It uses a pre-determined list of skills, which may or may not correspond with the skills that employers themselves are concerned about. Moreover, the skills are generic in nature, and not occupation specific. Skills are divided into groups (see below), and it is not possible to compare the importance of specific skills between groups (only within groups). Finally, the survey looks at skills of only two types of workers, highly skilled college graduates, and less skilled high school graduates (see below). These two groups are very heterogeneous, with a substantial variation in the skill set demanded from workers within a group. The upshot is that the survey’s results are very general in nature and as such are meant to highlight the importance of the skills gap problem, rather than to examine skill gaps specific to different types of workers and occupations. Put differently, the results are intended to inform the public debate on skills and education policy, rather than to identify specific skills-related problems. The note is structured as follows. Section one provides background information on the skill structure of employment, and presents evidence on a skills shortage in Armenia. Section two is central. It examines the demand for skills and the skills gap. It identifies skills that determine the employers hiring decisions, and skills that young job applicant most frequently lack. Section three focuses on firm organized training as a way of coping with a skills shortage. Section four concludes and discusses policy implications of the analysis.